THE CONSTITUTION IS OUR LAW, OUR HONOR AND DIGNITY, THE DEFENDER OF OUR RIGHTS (Web of Teachers: Inderscience Research, 2025)
This work examines in detail the role of the Constitution as the basic law of the state, the guarantor of the rights and freedoms of citizens, as well as a symbol of the honor and dignity of the nation. Particular attention is paid to the analysis of legal mechanisms that ensure the protection of human rights, as well as the importance of the Constitution in the formation of a legal culture and the strengthening of law and order. The study highlights the importance of upholding and respecting the Constitution to maintain stability and justice in society.